Identifying the predictors of turnover intention based on psychosocial factors of nurses during the COVID‐19 outbreak - Alireza Mirzaei; Hamed Rezakhani Moghaddam; Aghil Habibi Soola (Wiley, 2021)
Abstract Aims Because of the direct contact nurses have with patients, they are exposed to more stressful events during the outbreak of infectious diseases, which increases their turnover intention, highly impacting not only nurses, but also patients and organizations. The present study aimed to identify the predictors of turnover intention based on psychosocial factors in nurses of Ardabil pre‐hospital emergency and educational and medical centres during the COVID‐19 outbreak. Design The present descriptive‐analytical study was conducted in June, 2020. Methods A total of 479 nurses working in Ardabil pre‐hospital emergency and educational and medical centres to fight COVID‐19 were recruited for this study using the census method. Data were collected using the Demographic Information Questionnaire, Turnover Intention Questionnaire, Weiss & Marmar Impact of Event Scale‐Revised (IES‐R), General Health Questionnaire (12 C‐GHQ) and Job Content Questionnaire (JCQ). Data were analysed with SPSSv.22 software using correlation, t test, analysis of variance, multiple regression and descriptive tests. Results The mean turnover intention score of nurses was 41.73 with a standard deviation of 12.11. The results of correlation coefficient revealed a positive relationship between PTSD, general health, job demand and job strain with turnover intention (p ≤ .01) and a positive and significant relationship between social support and turnover intention (p ≤ .01). Multiple regression analysis showed that the variables of gender, marital status, work position, decision latitude, social support, job strain, general health and post‐traumatic stress disorder (PTSD) were predictors of turnover intention. Conclusion Job stressors during the COVID‐19 outbreak have led to an increase in nurses' turnover intention. Identifying and managing the factors related to job stressors will make it possible to prevent nurses' turnover intention in such critical situations.